GLOBAL PRODUCTION AND SALES CHAINS IN THE AGRICULTURE SPHERE: MODERN POLICY AND PRACTICE - GROMENKOVA, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the study of global production and sales chains in the agro-food sector, the peculiarities of the involvement of countries of the world in them, in particular, Ukraine. The policy and practice in this area, prospects for Ukraine, possible approaches to regulating the process of integration into agrarian and food global chains are analyzed. It was determined that the development of global chains of added value can have a number of positive manifestations in the field of agro-industrial complex, including the simplification of the mechanism of integration of countries into the global food market, the convergence of national food markets, the dissemination of progressive experience, and the promotion of sustainable development. There is a positive and significant relationship between FDI and indicators that characterize the level of the country’s involvement in agri-food global value chains, as well as the creation of domestic added value in global chains. This actualizes the issue of improving investment and trade policy, creating appropriate institutional conditions in the country, thanks to which it will be possible to more actively include Ukrainian representatives of the agro-food business in global production and sales chains. Among the important areas of improvement of institutional conditions are a clear, transparent and predictable investment policy, strong protection of investors (including compensation for expropriation), reliable protection of land use rights and land rights, as well as intellectual property rights, tax benefits. Dynamic agricultural innovation systems, in particular, well-developed research networks and innovation clusters, agri-food research institutions, and state advisory services can have a significant positive impact. The policy of state support for connections in supply chains can play an important role in promoting the development of business activity of multinational enterprises, which are the most powerful donors of direct investment in the world. Priorities may include a well-developed regulatory framework for contract farming and contract enforcement systems.